Principal Leadership and Merdeka Curriculum Implementation as Predictors of Elementary School Teacher Performance - Fatra Astaman; Bukman Lian; Pahlawan Pahlawan (Yayasan Sembilan Pemuda Indonesia, 2027)
This study examines the effects of principal leadership and the Merdeka Curriculum on teacher performance in elementary education, recognizing teacher performance as a central indicator of educational quality. A quantitative causal-correlational design was employed, involving 48 teachers from SD Negeri 4 Menanga, Semendawai Barat District, Ogan Komering Ulu Timur Regency, Indonesia. Data were collected through Likert-scale questionnaires, observation, and documentation. Instrument validity was tested using Pearson product-moment correlation, and reliability via Cronbach’s alpha. Analyses included descriptive statistics, normality, homogeneity, linearity, correlation, simple regression, and multiple regression. Principal leadership significantly and positively affected teacher performance (B = 1.205; t = 15.142; p < 0.001; R² = 0.649), as did the Merdeka Curriculum (B = 1.282; t = 20.159; p < 0.001; R² = 0.766). Simultaneously, both variables explained 81.2% of the variance in teacher performance (F = 265.744; p < 0.001). This study uniquely integrates leadership and curriculum reform as joint predictors of teacher performance within a rural elementary school context, an underexplored combination in existing literature. Findings emphasize the necessity for school administrators to combine instructional leadership with targeted curriculum assistance to optimize teacher effectiveness. This research provides empirical evidence that strategic leadership and responsive curriculum implementation are mutually reinforcing drivers of teacher performance, offering actionable insights for policymakers and school leaders in similar rural settings.